The opposition in Bahrain: a bellwether for the Gulf? - Bahry, Louay (Middle East policy, 1997)
The article traces back the history of the current opposition movement in Bahrain and examines its political, social and economic factors. It furthermore shows that it consists of two different movements which both seek political reform and so far have shown a high degree of unity. The older movement exists since the 1960s and 1970s, is in general of secular orientation and comprises Sunnis and Shia. The younger one appeared first shortly after the Islamic revolution in Iran but did not become a serious and active movement until the 1990s, is of religious orientation and consists of Shia only. As the article concludes it is this younger Shia movement which might cause greater sectarianism and extremism in the future. (DÜI-Mjr)